Сomparing temperature of subauroral mesopause over Yakutia with SABER radiometer data for 2002–2014 - Ammosova A.M.; Gavrilyeva G.A.; Ammosov P.P.; Koltovskoi I.I. (Solar-Terrestrial Physics, 2017)
We present the temperature database for the mesopause region, which was collected from spectral measurements of bands O2(0-1) and OH(6-2) with the infrared spectrograph SP-50 at the Maimaga station (63° N; 129.5° E) in 2002–2014. The temperature time series covers 11-year solar cycle. It is compared with the temperature obtained with the Sounding of the At-mosphere using Broadband Emission Radiometry in-strument (SABER, v.1.07 and v.2.0), installed onboard the TIMED satellite. We compare temperatures meas-ured during satellite passes at distances under 500 km from the intersection of the spectrograph sighting line with the hydroxyl emitting layer (~87 km) and oxygen emitting layer (~95 km). The time criterion is 30 min. We observe that there is a seasonal dependence of the difference between the ground-based and satellite measurements. The data obtained using SABER v2.0 show good agreement with the temperatures measured with the infrared digital spectrograph. The analysis we carried out allows us to conclude that a series of rotational temperatures obtained at the Maimaga station can be used to study temperature variations on different time scales including long-term trends at the mesopause height